Nicosia - concerted retailing and tourism strategies to awaken a neglected and sleeping beauty - Kaufmann, Rudi; Gronau, Werner; Sakkadas, Savvas (My University, 2011)
Nicosia, the last divided European city, is only able to skim a small portion of the tourist purchasing power compared to the other tourism strongholds of the island and, at the same time, does not utilize the existing cultural potential in an efficient way. Therefore, this paper aims to contribute to the valorisation of the existing potential in a customer oriented manner. Concerted international (UN Nicosia Master Plan) and national (Strategic Plan 2010) strategies reflect the intended revival endeavours. For this new orientation to be successful the paper hypothesizes an effective interplay between tourism and retailing to happen and, for this reason, analyses the motives and satisfaction levels of tourists to Nicosia with regards to both, tourism and retailing offers. The paper focuses on the tourist segment with higher educational levels (and implicitly higher financial potential) as the communication objectives foresee to position the island mainly in the mind of this segment. The paper concludes, in line with recent developments with regard to tourist consumer profiles, that the concept of authenticity plays an increasing role when explaining the satisfaction levels of this specific segment and provides practical recommendations. University of the Aegean.
Keywords: Retail; Tourism; Culture; Authenticty; Cyprus; Nicosia